Do Minimum Wages Reduce Poverty? A Case Study of Palangkaraya City - Rima Harati (Involvement International Journal of Business, 2025)
This study examines the impact of the regional minimum wage on poverty levels in Palangkaraya City from 2010 to 2024. The goal is to determine whether an increase in the minimum wage reduces poverty in the region. A simple linear regression model was used to analyze the effect of the regional minimum wage (independent variable) on poverty (dependent variable). Secondary data on the regional minimum wage and poverty rates were sourced from the Palangkaraya City Central Statistics Agency (BPS). Classical assumption tests, including normality, multicollinearity, and heteroscedasticity tests, were conducted to validate the regression model. The regression analysis found a significant negative relationship between the regional minimum wage and poverty in Palangkaraya City (coefficient = -6.080E-7, t = -5.561, p < 0.05). The normality and multicollinearity tests met the required assumptions, while heteroscedasticity was detected in the model. The study confirms that an increase in the regional minimum wage can significantly reduce poverty in Palangkaraya City. However, the presence of heteroscedasticity suggests that further model refinement is needed. Future research should focus on improving model accuracy and expanding the scope to include other factors influencing poverty.